Disturbed protein–protein interaction networks in metastatic melanoma are associated with worse prognosis and increased functional mutation burden. (5th July 2013) - Schramm, Sarah‐Jane; Li, Simone S.; Jayaswal, Vivek; Fung, David C. Y.; Campain, Anna E.; Pang, Chi N. I.; Scolyer, Richard A.; Yang, Yee Hwa; Mann, Graham J.; Wilkins, Marc R.
Summary: For disseminated melanoma, new prognostic biomarkers and therapeutic targets are urgently needed. The organization of protein–protein interaction networks was assessed via the transcriptomes of four independent studies of metastatic melanoma and related to clinical outcome and MAP‐kinase pathway mutations ( BRAF / NRAS ). We also examined patient outcome‐related differences in a predicted network of microRNAs and their targets. The 32 hub genes with the most reproducible survival‐related disturbances in co‐expression with their protein partner genes included oncogenes and tumor suppressors, previously known correlates of prognosis, and other proteins not previously associated with melanoma outcome. Notably, this network‐based gene set could classify patients according to clinical outcomes with 67–80% accuracy among cohorts. Reproducibly disturbed networks were also more likely to have a higher functional mutation burden than would be expected by chance. The disturbed regions of networks are therefore markers of clinically relevant, selectable tumor evolution in melanoma which may carry driver mutations.